Consumer Preferences and Willingness to Pay for Porang-Based Analog Rice - Viariani, Wahyu; Nurmalina, Rita; Harmini (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
Rice is a staple food for many people worldwide, especially in Asia, including Indonesians, with conventional white rice being the most commonly consumed type. However, conventional white rice has nutritional limitations and a high glycemic index, which can negatively impact health. This study explores consumer preferences and Willingness to Pay (WTP) for porang-based analogue rice as a healthier alternative. Using the Discrete Choice Experiment (DCE) method, data were collected from 150 respondents in Bogor, Indonesia, through voluntary response sampling. The results show that attributes such as porang rice type, softness, clear white colour, packaging, well-known brand, ease of preparation, longer shelf life, and health claims significantly influence consumer preferences. Consumers are willing to pay a higher price: IDR 46,040/kg for porang rice, IDR 58,600/kg for soft rice, IDR 43,338/kg for rice with a clear white colour, IDR 61,860/kg for packaged rice, IDR 61,389/kg for rice with a well-known brand, IDR 40,028/kg for rice that is easy to prepare, IDR 41,200/kg for rice with a longer shelf life, and IDR 90,401/kg for rice with health claims. These findings highlight the growing demand for healthier food options and provide valuable insights for producers and marketers to develop effective strategies. Emphasizing product quality and health benefits is crucial to increasing market acceptance of porang-based analogue rice.